Clinical and Esthetical Evaluation of 79 Lithium Disilicate Multilayered Anterior Veneers with a Medium Follow-Up of 3 Years - Malchiodi, Luciano; Zotti, Francesca; Moro, Tommaso; De Santis, Daniele; Albanese, Massimo (European Journal of Dentistry, 2019)
Objectives Primary aim of this study was to evaluate survival rate of lithium disilicate veneers in upper and lower anterior teeth. Secondary aims were to evaluate changing in proportions of teeth before and after restorations and to assess mean thickness of the veneers.Materials and Methods Seventy-nine upper and lower lithium disilicate veneers were made in 13 patients with worn teeth. Mean follow-up was 3 years. To perform anterior definitive rehabilitations, malocclusions and loss of vertical dimension were treated by full mouth rehabilitations to obtain proper occlusal conditions. Veneers were made of lithium disilicate core and fluorapatite-based ceramic stratification. Survival rate was calculated by Kaplan–Meier analysis. Changing in teeth proportion before and after restorations was analyzed by a paired t-test. Descriptive statistics of thickness values were also performed.Results One case of detachment was observed with a 98.7% survival rate. Teeth’s proportions were preserved although the first upper right incisor and canine changed in dimension.Conclusions Lithium disilicate veneers in esthetical rehabilitations of worn teeth proved to be an effective way of treatment in a medium follow-up of 3 years. Proportions seemed to be maintained with a minimum dental removal.
Keywords: lithium disilicate veneers; esthetical proportions; worn teeth